PENEGAKAN HUKUM TERHADAP PENOLAKAN MATA UANG LOGAM RUPIAH SEBAGAI ALAT TRANSAKSI PEMBAYARAN MENURUT PASAL 33 AYAT (2) UNDANG-UNDANNG NOMOR 7 TAHUN 2011 TENTANG MATA UANG DI KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR - Hamdani, Revky; Artina, Dessy; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Paper Rupiah and Metal Rupiah are the valid currency of the Republic of Indonesia in conducting payment transactions, based on Article 23 paragraph (1) of Law Number 7 of 2011 concerning Currency states that: or to settle obligations that must be fulfilled with Rupiah and / or no other financial transactions in the Territory of the Unitary Republic of Indonesia, unless there are doubts about the authenticity of the Rupiah.In Law No. 7 of 2011 on the Currency which is lex on the draft Criminal Code has been set up with clear that whoever the financial transaction in the territory of the Republic of Indonesia (Homeland) must use the rupiah, either in the form of fractional banknotes or coins. Thus, there is no reason for the public to reject rupiah coins as a means of buying and selling transactions. In Law Number 7 of 2011 concerning Currency which is the lex specialis of the Criminal Code Act has clearly stipulated that anyone who transacts financially in the territory of the Unitary Republic of Indonesia (NKRI) must use rupiah, both in the form of banknotes and coins. Thus, there is no reason for the public to reject rupiah coins as a means of buying and selling transactions.This research uses the typology of sociological legal research or also called non-doctrinal legal research, which is more specifically about the effectiveness of law. In this study the author uses the nature of descriptive research, because the author illustrates how law enforcement against the refusal of the Rupiah metal currency as a means of payment transactions according to Article 33 paragraph (2) of Law Number 7 of 2011 concerning Currency in the Kateman District of Indragiri Hilir Regency and to find out the inhibiting factors of law enforcement against the refusal of coins in Kateman Subdistrict, Indragiri Hilir Regency, and find out what solutions can be done to overcome barriers to law enforcement against denial of coins in Kateman Subdistrict, Indragiri Hilir Regency.The results of research conducted by the author are, firstly the implementation of how law enforcement is against rejection of coins, and provides the best solution so that the factors of law enforcement against rejection of the law are carried out according to what the writer and the public expect Keywords: Law enforcement - denial of coins